4D-quantitative proteomics signature of asthenozoospermia and identification of extracellular matrix protein 1 as a novel biomarker for sperm motility. (24th November 2021) - Yang, Jie; Liu, Qunlong; Yu, Bohai; Han, Baoquan; Yang, Bo
Abstract : 4D mass spectrometry quantifies 1430 differential abundant proteins in asthenozoospermic sperm samples. Further, integrative analysis identifies ECM1 as a novel biomarker related to sperm motility. Abstract : Asthenozoospermia (AZS), diagnosed by reduced sperm motility, is one of the major causes of male infertility. However, AZS has no effective therapeutic treatment and the underlying molecular mechanism remains largely unclear. In this study, state-of-the-art 4D-quantitative proteomics analysis was used to compare the protein profiling between 7 normozoospermic and 11 asthenozoospermic sperm samples. Overall, 4718 proteins were identified and 1430 differential abundant proteins were found in the two groups. The differentially expressed proteins were analyzed by GO and KEGG. The core deregulated proteins and pathways associated sperm motility dysfunction included energy metabolism and the sperm structure. Integrative analysis further identified extracellular matrix protein 1 (ECM1) as a novel biomarker related to AZS. Our study could provide new insights into the molecular basis of low sperm motility. The mass spectrometric data are available via ProteomeXchange with identifier PXD027637.